2019
DOI: 10.1029/2018jc014866
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Upper Ocean Water Masses as Inferred From Argo Array

Abstract: Interannual variability of Ocean Heat Content (OHC) is intimately linked to ocean water mass changes. Water mass characteristics are imprinted at the ocean surface and are modulated by climate variability on interannual to decadal time scales. In this study, we investigate the water mass change and their variability using an isopycnal decomposition of the OHC. For that purpose, we address the thickness and temperature changes of these water masses using both individual temperature‐salinity profiles and optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 79 publications
(173 reference statements)
12
65
0
Order By: Relevance
“…A prominent water mass of the region, the Sub-Antarctic Mode Water (SAMW), is identified around the southern subtropical gyres as a layer of low potential vorticity (PV) acquired during its formation (McCartney, 1977). Variability of the SAMW properties on decadal and longer time scales has been reported by recent studies (e.g., Bindoff & McDougall, 2000;Gille, 2002;Bryden et al, 2003;Gao et al, 2018;Kolodziejczyk et al, 2019;Portela et al, 2020). Among others, Gao et al (2018) showed that the SAMW has significantly thickened, deepened, and warmed during the period from 2005 to 2015.…”
Section: Introductionsupporting
confidence: 54%
“…A prominent water mass of the region, the Sub-Antarctic Mode Water (SAMW), is identified around the southern subtropical gyres as a layer of low potential vorticity (PV) acquired during its formation (McCartney, 1977). Variability of the SAMW properties on decadal and longer time scales has been reported by recent studies (e.g., Bindoff & McDougall, 2000;Gille, 2002;Bryden et al, 2003;Gao et al, 2018;Kolodziejczyk et al, 2019;Portela et al, 2020). Among others, Gao et al (2018) showed that the SAMW has significantly thickened, deepened, and warmed during the period from 2005 to 2015.…”
Section: Introductionsupporting
confidence: 54%
“…Note that the medium SAMW trend is small and nonsignificant. The volume trend of the dense and light SAMW is coincident with the two‐layer opposite thickness trend for the SIO SAMW over 2006–2015 (Figure 5 in Kolodziejczyk et al, 2019). There appears to be a decadal signal associated with this volume variation (Figures 2a and 2b), which needs to be confirmed by longer time observations.…”
Section: Samw Volume Change and Spatial Distributionmentioning
confidence: 53%
“…In the past decade, most of the ocean warming measured by the near-global array of Argo floats occurred in the Southern Hemisphere, largely associated with changes in SAMW in the southern Pacific and Indian Oceans (Desbruyères et al 2017;Gao et al 2018;Häkkinen et al 2016;Kolodziejczyk et al 2019;Llovel and Terray 2016;Portela et al 2020;Roemmich et al 2015). The SAMW formation is vigorous in the south Indian Ocean (SIO), attracting much attention recently.…”
Section: Introductionmentioning
confidence: 99%